Optimisation of Calophyllum inophyllum seed oil nanoemulsion as a potential wound healing agent - Elnaz Saki; Vinuthaa Murthy; Roshanak Khandanlou; Hao Wang; Johanna Wapling; Richard Weir (BMC, 2022)
Abstract Background Efficient delivery systems of Calophyllum inophyllum seed oil (CSO) in the form of nanoemulsion were optimised to enhance its stability and ensure its therapeutic efficiency as a potential agent for various biomedical applications. Method Response Surface Methodology (RSM) was used to determine the effects of independent variables (oil, surfactant, water percentage and homogenisation time) on physicochemical characteristics, including droplet size, polydispersity index and turbidity. Results The optimised CSO nanoemulsion (CSONE) has a 46.68 nm particle size, 0.15 Polydispersity index value and 1.16 turbidity. After 4 weeks of storage at 5 ± 1 °C and 25 ± 1 °C, the CSONE was physically stable. The optimised CSO nanoemulsion showed enhancement in cell viability and wound healing in baby hamster kidney a clone BHK-21 (BSR) cells as compared to the CSO. The wound healing property of CSONE was higher than CSO. Conclusion Thus, our in vitro wound healing results demonstrated that CSO in the nanoemulsion form can promote wound healing by enhancing the proliferation and migration of epidermal cells. Graphical Abstract The coarse emulsion of Calophyllum inophyllum seed oil nano emulsion was prepared using high shear homogeniser techniques. The optimised CSONE with the droplet size of 46.68 nm was prepared from a mixture of CSO, Tween 80, and high pure water (HPW), then used for the biological investigation. The in vitro cell monolayer scratch assay revealed that CSONE in the lowest concentration of CSO resulted in 100% wound closure after 48 hrs. The optimised CSO nanoemulsion was found to be a promising and effective approach in the treatment of wounds by boosting the proliferation and migration of epidermal cells.